Transient Ischemic Attack and Carotid Web - Hu, H. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Carotid web was recognized as a cause of ischemic stroke. We sought to determine the clinical and imaging profiles of patients with a carotid web as well as its association with TIA. MATERIALS AND METHODS: A retrospective review of carotid CT angiography studies and brain MR imaging in patients with TIA during the past 3 years (n = 135) was performed to determine the presence of carotid webs by 2 experienced neuroradiologists according to previously published criteria. Demographics and clinical and imaging characteristics are shown by descriptive statistics for patients with an identified carotid web. The agreement in the detection of carotid webs between 2 neuroradiologists was examined using κ statistics. RESULTS: There were 12 (8.9%) carotid webs at the symptomatic bifurcation and 1 carotid web (0.7%) at the asymptomatic bifurcation, and no hyperintensity was seen on DWI of these 12 patients. Eight of these 12 (75%) patients with a carotid web were women. None of the 12 patients with a carotid web had major risk factors or other causes of TIA. Fair-to-good interobserver agreement (κ = 0.87) was seen for diagnosing a carotid web with CT angiography. The rate (10/12, 83.3%) of short-term recurrent episodes of TIA in patients with TIA with a carotid web was significantly higher than that of patients without a carotid web (15/123, 12.2%) (P < .001). CONCLUSIONS: The incidence of carotid web in patients with TIA was 8.9%. There is an association between carotid web and patients with TIA without other identified risks. Carotid web may be an underestimated risk factor for TIA.